2017
DOI: 10.1016/j.colsurfa.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing activity of cuttlefish gelatin gels and films enriched by henna (Lawsonia inermis) extract

Abstract: The in vivo wound-healing potential of gels and films based on cuttlefish skin gelatin (CSG) incorporated with aqueous henna extract (AHE) (at 50 and 500 µg/ml) was studied.Since wound healing is related to reactive oxygen species (ROS), this study was first conducted to evaluate the antioxidant activity of AHE by DPPH radical-scavenging, β-carotene-linoleate bleaching, and reducing power assays. The major volatile compounds were lawsone, dimethyl sulfoxide, dimethyl sulfide, eugenol and maltol. The finding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…These steps can be characterized into four highly programmed phases such as hemostasis, inflammation, proliferation and remodeling [2,6,[12][13][14][15][16]. All phases of healing must occur in suitable sequence for successful healing as a natural phenomenon [6,12,13] but sometimes complex multifactorial process of wound healing can be delayed or failed by unwanted effects such as presence of free radicals [12,17] or microbial infections [5,12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…These steps can be characterized into four highly programmed phases such as hemostasis, inflammation, proliferation and remodeling [2,6,[12][13][14][15][16]. All phases of healing must occur in suitable sequence for successful healing as a natural phenomenon [6,12,13] but sometimes complex multifactorial process of wound healing can be delayed or failed by unwanted effects such as presence of free radicals [12,17] or microbial infections [5,12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The zinc oxide incorporated chitosan/PVA nanofibrous mats shows noted scavenging property . The proton contributing capability of phenolic groups in henna leaves convert free radicals to a stable product and arrest radical chain reaction . Additionally, lawsone supports in modulating redox signalling by different pathways .…”
Section: Resultsmentioning
confidence: 99%
“…Usually, lawsone has poor solubility, in order to maintain its bioavailability incorporation with bioactive polymers was followed . The histopathological analysis of aqueous henna extract loaded Cuttlefish gelatin film shows pronounced antioxidant and wound healing . It has been reported that the lawsone loaded hydroxyethyl cellulose/PVP hydrogel and PLLA/gelatin nanofiber shows good antibacterial and biocompatibility towards fibroblast cells.…”
Section: Introductionmentioning
confidence: 82%
“…Clinically, chronic wounds usually refer to wounds caused by various reasons, which cannot automatically restore their functional integrity within three months, and also have no tendency to heal . More seriously, due to the influence of potential physiological conditions, such as diabetes, chronic wounds not only heal slowly but are also often prone to recurrence .…”
Section: Causes and Healing Of Woundsmentioning
confidence: 99%
“…If inflammation is not controlled, it will lead to the self‐secretion of extracellular polysaccharide matrix, which will protect bacteria from the host's immune response and antibiotic therapy . In addition, persistent hyperglycemia would elevate the levels of advanced glycation end products (AGEs) in the blood, which can directly induce high concentration of ROS . This may disrupt the redox balance of the cells, causing metabolic disorders that further impair the structural integrity of the blood vessels and tissue regeneration …”
Section: Causes and Healing Of Woundsmentioning
confidence: 99%